Can small business contribute more to sustained growth and competitiveness of the Jamaican economy? - Hamilton, Trevor (1992)
Outlines the role of small businesses and lists three main sources of opportunities as: the privatization programme; the emerging export opportunities; and, high growth sector spin-offs.